PENERAPAN KONSEP GEOGRAFI PADA BUKU TEKS GEOGRAFI TERBITAN CEMPAKA PUTIH DAN SOAL ULANGAN HARIAN GEOGRAFI DI KELAS XII IPS SMA NEGERI 8 PADANG - amalia ramadhani ruslan; Ahyuni Ahyuni (JURUSAN GEOGRAFI FIS UNP, 2021)
This study was written to analyze how much the application of the concept of geography in the Cempaka Putih geography textbooks class XII and daily test question that currently used in SMAN 8 Padang. This research used quantitative methode with content analyze approach. The data analyze used percentage technique. The results show that the total amount of paragraph reading in the textbooks are 241 paragraph very low with percentage 16,59%, total of question in geography textbooks are 115 with percentage 10,43% including very low category, and total of daily test question are 50 question with percentage 6% including very low category. So, the conclusion is the application of the concept of geography in geography textbooks and daily test question class XII was dominated by very low category.